Carbon and energy taxes in a small and open country - S. Solaymani (Global Journal of Environmental Science and Management)
Malaysia, as a small and developing country, must reduce carbon emissions because the country is one of the top CO2-emitting countries in the ASEAN region. Therefore, the current study implements two environmental tax policies; carbon and energy taxes, in order to examine the impacts of these policies on the reduction of carbon emission in the whole of the economy by applying a computable general equilibrium model. Since the whole of the government revenue from these tax policies is transferred to all household and labor types through two schemes, a lump sum tax, and a labor tax, respectively, it is assumed that there is revenue neutrality in the model for the government. The findings from simulated scenarios indicate that the carbon tax policy is the more efficient policy for reducing CO2 emission, in both transferring schemes, while its impact on macroeconomic variables is almost lower than the equivalent energy tax. The carbon tax is more effective than the energy tax for Malaysia to achieve 40% carbon reduction target in comparison with its 2005 level. The carbon tax, compared to the energy tax, also leads to more decrease in consumption of fossil fuels. The carbon tax policy, in comparison with the energy tax, due to revenue recycling causes much more increase in the welfare of rural and urban households in Malaysia, especially the welfare of rural (lower income) households.